A case report of frozen elephant trunk combined with endovascular treatment for acute aortic dissection of Kommerell's diverticulum involving right aortic arch and descending aorta. Issue 15 (April 2018) - Guo, Hongwei; Sun, Xiaogang; Yu, Cuntao; Shu, Chang
Abstract: Rationale: Acute aortic dissection of Kommerell's diverticulum in the right aortic arch is extremely rare. There are several different procedures for the disease. With advances in endovascular treatment, hybrid surgical and endovascular management may provide a treatment of choice for this kind of disease. Patient concerns: A 43-year-old man was admitted to the hospital with intermittent pain of left arm, chest, and back. Diagnoses: Computed tomography demonstrated an aberrant left subclavian artery originating from Kommerell's diverticulum in the right aortic arch, acute aortic dissection of Kommerell's diverticulum involving arch and descending aorta. Interventions: Total arch replacement combined with frozen elephant trunk was performed to create an adequate landing zone through a median sternotomy by circulatory arrest. Thoracic endovascular aortic repair was performed to isolate Kommerell's diverticulum from descending aorta completely, extending from the frozen elephant trunk to the distal descending aorta at the same time. Outcomes: The patient got an uneventful postoperative course. Lessons: Hybrid surgical and endovascular management is a safe and effective procedure for this rare disease.